The psychophysiological technology with biofeedback in complex rehabilitation of post-stroke patients: a randomized controlled study - Elena V. Kostenko; Anastasia V. Kotelnikova; Liudmila V. Petrova; Irena V. Pogonchenkova; Maksim S. Filippov (Вестник восстановительной медицины)
INTRODUCTION. Psychophysiological technologies with biofeedback (BFB) are a promising area of in medical rehabilitation (MR) for post-stroke patients.